2017
DOI: 10.3390/insects8010006
|View full text |Cite
|
Sign up to set email alerts
|

Complex Messages in Long-Term Monitoring of Regal Fritillary (Speyeria idalia) (Lepidoptera: Nymphalidae) in the State of Wisconsin, USA, 1988–2015

Abstract: The regal fritillary (“regal”) (Speyeria idalia) is endangered in Wisconsin, USA, and declining and at risk range-wide. During 1988–2015, we surveyed 24 known regal sites and >100 areas of potential habitat in Wisconsin. We recorded 9037 individuals in 742.7 km on the peak survey per year at occupied sites. At six sites surveyed over 5–25 years, we found regal fritillaries in only one year, mostly in the latter half of the study. The three populations in the state with more favorable trends than the median had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Using transect counts, Swengel (1997) estimated adult densities of 2130, 800 and 290 individuals km −2 for the sympatric S. cybele (Fabricius, 1775), S. aphrodite (Fabricius, 1787) and S. idalia , respectively, at American Midwest prairie remnants, with the most threatened species being locally least abundant. Swengel and Swengel (2001) obtained consistently higher (≈3–6 times) transect counts for the less threatened S. aphrodite than for the declining S. idalia in a 10‐year study in Wisconsin. Low transect counts were also reported for the rapidly declining A. adippe in Britain (Ellis et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Using transect counts, Swengel (1997) estimated adult densities of 2130, 800 and 290 individuals km −2 for the sympatric S. cybele (Fabricius, 1775), S. aphrodite (Fabricius, 1787) and S. idalia , respectively, at American Midwest prairie remnants, with the most threatened species being locally least abundant. Swengel and Swengel (2001) obtained consistently higher (≈3–6 times) transect counts for the less threatened S. aphrodite than for the declining S. idalia in a 10‐year study in Wisconsin. Low transect counts were also reported for the rapidly declining A. adippe in Britain (Ellis et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…This could have implications for the future persistence of this species if patterns of precipitation and temperature change in the future. Swengel and Swengel (2017) indicated that regal distributions have been gradually shifting northward and that this trend would likely continue as average temperatures increase in the Great Plains and Midwest. Our model allowed us to examine a simple scenario in which we simulated a systematic 2°C increase across the region.…”
Section: Discussionmentioning
confidence: 99%
“…It is restricted to xeric tallgrass prairie remnants and it is rare or absent from former range east of the Appalachians. There are many extant populations, but the species has suffered severe population declines and its range continues to contract [ 20 ] S. idalia is almost gone from areas east of the Mississippi River, and it is imperiled in Illinois, Indiana, Pennsylvania, Virginia, and Wisconsin [ 20 , 21 ]. The biggest obvious threat to S. idalia is loss of its prairie habitat to development and agriculture, and the principal conservation need is to protect and manage its remaining prairie habitat [ 22 ].…”
Section: Examples Of Threatened Species/subspeciesmentioning
confidence: 99%
“…The majority of habitat losses have resulted from human activities, including land development for agriculture, commercial, and residential uses, but climate change now represents an additional risk factor. In some cases, Speyeria habitat has been reduced in a mosaic pattern, leaving relatively small islands of suitable habitat that may be inadequate for long-term population survival [ 21 , 26 ]. In addition to the inbreeding and reduced gene flow problems mentioned previously, small populations also face an increased risk of extinction from stochastic events such as severe weather or fires [ 79 ].…”
Section: Conservation Issuesmentioning
confidence: 99%